Physical Potential of National Traditions in Physical Education Class: Potensi Fisik Tradisi Nasional di Kelas Pendidikan Jasmani - Mirkhojiddinovna, Khudoynazarova Gullola (Indonesian Journal of Education Methods Development, 2022)
This paper analyzes major points of the physical potential of national traditions in physical education classes. In this case, research has been pinpointed on the theoretical and methodological points of the physical education classes. In conclusion, major aspects were discussed pros and cons of the issue.